2019
DOI: 10.2174/1566524019666190325143412
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Potential Substrates of the Depalmitoylation Enzyme Acyl-protein Thioesterase 1

Abstract: Background: The homeostasis of palmitoylation and depalmitoylation is involved in various cellular processes, the disruption of which induces severe physiological consequences. Acyl-protein thioesterase (APT) and palmitoyl-protein thioesterases (PPT) catalyze the depalmitoylation process. The natural mutation in human PPT1 caused neurodegenerative disease, yet the understanding of APT1 remains to be elucidated. While the deletion of APT1 in mice turned out to be potentially embryonically lethal, the decoding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Validated proteins also include all known PPT1 substrates—CSPα, Goα, and F1 subunit O of mitochondrial ATP synthase—and exclude substrates of other depalmitoylating enzymes, such as PSD-95, an abundant synaptic protein that is exclusively depalmitoylated by ABHD17A, 17B, and 17C [ 40 ]. Putative APT1 substrates such as RAB9A, RAB6A, N-RAS, R-RAS, GAP-43, and SNAP-23 are also excluded [ 20 , 41 , 42 ]. We also screened our results against a PPT1 interactome dataset ( n = 64) [ 24 ] and found 4 high-confidence substrates (DYL2, LDHB, STXB1, and THY1) and 4 medium-confidence substrates (DYN1, GBB2, TERA, and VA0D1) to be present.…”
Section: Resultsmentioning
confidence: 99%
“…Validated proteins also include all known PPT1 substrates—CSPα, Goα, and F1 subunit O of mitochondrial ATP synthase—and exclude substrates of other depalmitoylating enzymes, such as PSD-95, an abundant synaptic protein that is exclusively depalmitoylated by ABHD17A, 17B, and 17C [ 40 ]. Putative APT1 substrates such as RAB9A, RAB6A, N-RAS, R-RAS, GAP-43, and SNAP-23 are also excluded [ 20 , 41 , 42 ]. We also screened our results against a PPT1 interactome dataset ( n = 64) [ 24 ] and found 4 high-confidence substrates (DYL2, LDHB, STXB1, and THY1) and 4 medium-confidence substrates (DYN1, GBB2, TERA, and VA0D1) to be present.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of human LYPLA1 (APT1) gene ablation in HEK293T cells by CRISPR/Cas9 has previously been reported. 29 Homogeneous clones of APT1 −/− cells were derived by single cell sorting of eGFP-and DsRed2-positive populations into 96-well microplates. The expanded monoclonal mutant cells were screened by Western blot analysis using rat anti-human APT1 polyclonal antibody, which showed that LPLA1 (APT1)protein was not expressed.…”
Section: Generation Of Apt1 −/− Hek293t Cells By Crispr/cas9mentioning
confidence: 99%
“…We reasoned that if Ppt1‐deficiency decreases APT1 levels it may suppress depalmitoylation of H‐Ras, thereby increasing its level on the plasma membrane where the activation of H‐Ras signaling pathway may stimulate the proliferation and activation of the innate immune cells in the CNS leading to neuroinflammation. Since Cln1 /Ppt1 is expressed in all cells and tissues, we used both Ppt1‐deficient Cln1 −/− mice, 24 which mimic INCL, 25 HEK293T cells in which the CLN1/PPT1 gene is ablated by CRISPR/Cas9, APT1‐KO HEK293T cells, 29 cultured INCL fibroblasts as well as those from Cln1 −/− mice as models. Finally, we sought to understand the neuroprotective mechanism of a Ppt1‐mimetic small molecule, N‐tert (Butyl) hydroxylamine (NtBuHA) 30 …”
Section: Introductionmentioning
confidence: 99%
“…It also excludes proteins that have been identified as substrates of other depalmitoylating enzymes; for example, PSD-95, an abundant synaptic protein that is exclusively depalmitoylated by ABHD17 (Yokoi et al, 2016). Putative APT1 substrates such as RAB9A, RAB6A, N-RAS, R-RAS, GAP-43, and SNAP-23 are also excluded (Duncan and Gilman, 1998;Kong et al, 2013;Liu et al, 2019).…”
Section: Secondary Validation Screen For Ppt1 Substratesmentioning
confidence: 99%
“…Validated proteins also include all known PPT1 substrates-CSPα, Goα, and F1 subunit O of mitochondrial ATP synthase-and exclude substrates of other depalmitoylating enzymes, such as PSD-95, an abundant synaptic protein that is exclusively depalmitoylated by ABHD17A, 17B, and 17C (Yokoi et al, 2016). Putative APT1 substrates such as RAB9A, RAB6A, N-RAS, R-RAS, GAP-43, and SNAP-23 are also excluded (Duncan and Gilman, 1998;Kong et al, 2013;Liu et al, 2019). We also screened our results against a PPT1 interactome dataset (Sapir et al, 2019) and found 4 high-confidence substrates (DYL2, LDHB, STXB1, THY1) and 7 medium-confidence substrates (DYN1, KIF5C, SSDH, SYT2, TERA, UBA1, VA0D1) to be present.…”
Section: Direct Depalmitoylation With Ppt1 Validates Putative Synaptic Substratesmentioning
confidence: 99%